Insulating powder and preparation method thereof
By constructing a multi-layered anti-corrosion system using fluorine-modified montmorillonite, graphene oxide-polyaniline composite material, and perfluorooctyltriethoxysilane, the performance degradation problem of insulating powder under acidic and alkaline environments was solved, and stability and performance improvement were achieved in complex environments.
Patent Information
- Application Number
- CN202511384227.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-12-05
AI Technical Summary
Existing insulating powders are prone to degradation and performance degradation in acidic and alkaline environments, and cannot maintain a synergistic balance of corrosion resistance, insulation, thermal stability and mechanical properties in complex environments.
A dense hydrophobic layer was constructed using fluorine-modified montmorillonite, fluorine-modified graphene oxide-polyaniline composite material, and perfluorooctyltriethoxysilane. Combined with a cross-linked network, the structural stability was enhanced. Nano-boron nitride was used to construct an efficient thermal conduction pathway, and glass fiber was used to improve mechanical strength.
It is stable over a wide pH range, blocks the penetration of acid and alkali media, maintains insulation performance, improves heat dissipation performance and mechanical strength, and is compatible with existing production equipment without modification.
Smart Images

Figure CN121064699A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of insulating materials, in particular to an insulating powder and a preparation method thereof. BACKGROUND
[0002] Insulating powder is widely used in electrical equipment in special environments such as chemical industry, ocean, metallurgy, etc. The long-term corrosion of acid-base medium in these scenarios poses strict requirements on the corrosion resistance and insulation stability of insulating materials. Current mainstream insulating powder is mostly based on epoxy resin as the matrix, with aluminum hydroxide, boron nitride and other fillers. Although it can meet the conventional insulation requirements, it is prone to performance degradation in acid-base environments. The interface between the resin matrix and the filler of traditional products is easily penetrated by acid-base medium, leading to degradation of the matrix and shedding of the filler, which in turn causes a significant decrease in volume resistivity and dielectric strength, and even causes short circuit failure of the equipment.
[0003] To improve corrosion resistance, the industry often uses methods such as increasing the thickness of the coating or adding a single acid-resistant filler, but the effect is limited. Simply thickening the coating increases the volume of the equipment and internal air bubbles are easily produced; adding acid-resistant fillers such as glass flake can extend the penetration path, but they have poor compatibility with the resin, easily forming interface voids and thus reducing insulation performance. Some products attempt to introduce fluorine-containing compounds, but most are simple physical mixtures, with uneven dispersion of fluorine elements, making it difficult to form a continuous corrosion-resistant layer, and easily causing antagonism with other components, affecting thermal stability and mechanical strength.
[0004] In addition, the thermal conductivity and mechanical properties of traditional insulating powder in acid-base environments are also easily damaged. Acid-base corrosion can destroy the network structure of the heat-conducting filler, leading to a decrease in heat dissipation performance and accelerated insulation aging due to heat accumulation during equipment operation; at the same time, degradation of the resin matrix can increase the brittleness of the material and reduce the impact strength, making it unable to withstand external forces such as equipment vibration. In the face of increasingly complex acid-base application scenarios, existing insulating powder has obvious deficiencies in the synergistic balance of corrosion resistance, insulation, thermal stability and mechanical properties. Developing insulating powder with excellent acid-base resistance and comprehensive performance has become the key to solving the problem of safe operation of electrical equipment in special environments. SUMMARY
[0005] (I) Technical problems solved In view of the deficiencies of the prior art, the present application provides an insulating powder and a preparation method thereof.
[0006] (II) Technical solutions An insulating powder comprises, by weight parts: epoxy resin 15-25 parts, aluminum hydroxide 10-20 parts, nano boron nitride 5-12 parts, silane coupling agent KH-560 1-3 parts, polytetrafluoroethylene micro powder 3-8 parts, fluorine modified montmorillonite 2-6 parts, melamine cyanurate 4-9 parts, nano titanium dioxide 2-5 parts, fluorine modified graphene oxide-polyphenylamine composite material 1-4 parts, pentaerythritol stearate 0.5-2 parts, nano zinc oxide 1-3 parts, glass fiber 5-10 parts, cage type silsesquioxane-polyimide copolymer 2-5 parts, ferrocene epoxy resin 1-4 parts, perfluorooctyl triethoxysilane 0.5-2 parts; a hydrophobic corrosion-resistant layer is constructed by introducing fluorine elements, combined with a cross-linked network to enhance the structural stability, realizing the synergy of excellent acid and alkali resistance and insulation performance.
[0007] Preferably, the fluorine modified montmorillonite is subjected to composite modification treatment with cetyltrimethylammonium bromide and potassium perfluorooctyl sulfonate; the amount of cetyltrimethylammonium bromide is 8-12% of the mass of the montmorillonite, and the amount of potassium perfluorooctyl sulfonate is 3-5% of the mass of the montmorillonite; the fluorine content of the modified montmorillonite is 3-5wt%, the interlayer spacing is 2.5-4.0nm, the particle size is 1-5μm, and the water content is ≤1.0%.
[0008] Preferably, the addition amount of perfluorooctyl triethoxysilane is preferably 0.8-1.5 parts, and the fluoralkyl chain in the molecule reacts with the molecular chain of the epoxy resin to form a dense fluorosilane modified layer on the surface and inside of the insulating powder.
[0009] Preferably, the fluorine modified graphene oxide-polyphenylamine composite material is prepared by fluorine aniline graft modification; the mass ratio of graphene oxide to polyaniline is 1:3-1:5, and the amount of fluorine aniline is 20-25% of the mass of aniline monomer; the fluorine element content of the modified composite material is 5-8wt%, the electrical conductivity is ≤10⁻ 8 S / m, and the particle size is 50-200nm.
[0010] Preferably, the epoxy resin is a compound of bisphenol A type epoxy resin and fluorine-containing epoxy resin in a mass ratio of 4:1; the epoxy value of the bisphenol A type epoxy resin is 0.48-0.54eq / 100g, and the softening point is 85-95℃; the fluorine-containing epoxy resin is a perfluorobutyl glycidyl ether type, the fluorine content is 10-15wt%, the epoxy value is 0.35-0.40eq / 100g, and the softening point is 70-80℃.
[0011] Preferably, the nano boron nitride has a hexagonal structure and is subjected to surface treatment with perfluorooctanoic acid; the amount of perfluorooctanoic acid is 5-8% of the mass of the nano boron nitride; after treatment, the surface fluorine coverage of the nano boron nitride is ≥30%, the particle size is 50-100nm, the purity is ≥99%, and the thermal conductivity is ≥300W / (m・K).
[0012] Preferably, the insulating powder comprises by weight: epoxy resin 18-22 parts, aluminum hydroxide 13-17 parts, nano boron nitride 7-10 parts, silane coupling agent KH-560 1.5-2.5 parts, polytetrafluoroethylene micro powder 4-6 parts, fluorine modified montmorillonite 3-5 parts, melamine cyanurate 5-8 parts, nano titanium dioxide 3-4 parts, fluorine modified graphene oxide-polyaniline composite 2-3 parts, pentaerythritol stearate 1-1.5 parts, nano zinc oxide 1.5-2.5 parts, glass fiber 6-8 parts, cage type silsesquioxane-polyimide copolymer 3-4 parts, ferrocene-based epoxy resin 2-3 parts, perfluorooctyl triethoxysilane 0.8-1.5 parts; the preferred formula is soaked in 10% hydrochloric acid and 10% sodium hydroxide solution for 168 hours, and the performance retention rate is ≥88%.
[0013] Preferably, the preparation method of the insulating powder comprises: S1, aluminum hydroxide, nano boron nitride, nano titanium dioxide, and nano zinc oxide are weighed by weight parts, placed in a mixer and stirred at 500-800 rpm for 10-15 minutes to mix evenly; transferred to an oven and dried at 100-120°C for 2-3 hours to remove water, cooled to 40-50°C, and then silane coupling agent KH-560 and perfluorooctyl triethoxysilane are added, placed in a high-speed mixer and stirred at 1500-2000 rpm for 30-40 minutes to evenly coat the coupling agent and fluorosilane on the surface of the powder; S2, add epoxy resin, ferrocene-based epoxy resin, polytetrafluoroethylene micro powder, and fluorine modified montmorillonite, transfer to a twin-screw mixer, heat to 80-90°C for melting and mixing, stir at 800-1000 rpm for 20-30 minutes, control the vacuum degree to -0.08 to -0.09 MPa to remove bubbles and enhance the compatibility of the components; S3, cool to 60-70°C, add melamine cyanurate, fluorine modified graphene oxide-polyaniline composite, pentaerythritol stearate, and cage type silsesquioxane-polyimide copolymer, keep stirring at 800-1000 rpm for 15-20 minutes to ensure uniform dispersion of each component; S4, add glass fiber, cool to 50-60°C, and reduce the stirring speed to 300-500 rpm for 10-15 minutes; transfer to a twin-screw extruder for granulation, the temperature of each zone of the extruder is 100-110°C for feeding, 110-120°C for compression, and 120-130°C for homogenization, and the die temperature is 110-120°C; freeze and crush to -50 to -40°C, and pass through a 200-300 mesh sieve to obtain the finished product.
[0014] Preferably, the preparation method of the fluorine modified montmorillonite comprises: taking montmorillonite and adding it into deionized water to prepare a 5-10 wt% suspension, stirring at 80-90°C and 500-600 rpm for 2-3 hours to fully exfoliate and disperse the montmorillonite; adding cetyltrimethylammonium bromide and potassium perfluorooctyl sulfonate into the suspension, the amount of cetyltrimethylammonium bromide being 8-12% of the mass of the montmorillonite, and the amount of potassium perfluorooctyl sulfonate being 3-5% of the mass of the montmorillonite, maintaining 80-90°C, 500-600 rpm stirring and reacting for 4-6 hours to allow the modifiers to insert into the interlayer of the montmorillonite; after the reaction is completed, filtering to collect the product, repeatedly washing with deionized water until there is no bromide ion in the filtrate, drying in an oven at 100-110°C for 8-10 hours, crushing and passing through a 100-mesh sieve to obtain the fluorine modified montmorillonite.
[0015] Preferably, the preparation method of the fluorine modified graphene oxide-polyaniline composite material comprises: taking graphene oxide and adding it into deionized water to prepare a 0.5-1.0 mg / mL suspension, ultrasonic treatment at 300-400 W for 30-40 minutes; adding 3-aminopropyltriethoxysilane in an amount of 3-5% of the mass of the graphene oxide, stirring at 50-60°C under nitrogen protection and 500-600 rpm for 2-3 hours to complete the amination modification; cooling to 20-25°C, adding aniline and fluoraniline mixed monomers, the mass ratio of aniline to fluoraniline being 4:1, and the mass ratio of graphene oxide to the total mass of the mixed monomers being 1:3-1:5, adding 10 wt% ammonium persulfate solution after stirring for 30 minutes, the molar ratio of ammonium persulfate to the mixed monomers being 1:1.2, and the dropping time being 30-40 minutes; cooling to 0-5°C and reacting for 6-8 hours; collecting the product by centrifugation at 8000-10000 rpm for 15-20 minutes, washing with 1 mol / L hydrochloric acid and deionized water alternately until the pH is 6.5-7.5, vacuum drying at 60-70°C for 12-15 hours, and ball milling at 300-500 rpm for 1-2 hours to obtain the fluorine modified graphene oxide-polyaniline composite material.
[0016] (Three) Beneficial technical effects Compared with the existing technology, the beneficial effects of the present application are: 1. Through the synergistic effect of the fluorine modified montmorillonite, the fluorine modified graphene oxide-polyaniline composite material and the perfluorooctyl triethoxysilane, a multi-level corrosion-resistant system is constructed. The fluorine element is uniformly distributed to form a dense hydrophobic layer to block the penetration of acid and alkali media; the composite modified filler is closely combined with the resin matrix to avoid interfacial corrosion and ensure the long-term stability of the material in a wide pH range environment, effectively solving the problems of easy degradation and rapid performance decay of traditional products.
[0017] 2. Fluorine-modified composite material and cage-type silsesquioxane-polyimide copolymer synergistic reinforcement insulation network ensures stable insulation performance in acid and alkali environment; nano-boron nitride after surface treatment constructs efficient heat conduction path, and the heat dissipation performance is not affected by acid and alkali corrosion, balancing the contradiction between corrosion resistance and heat dissipation.
[0018] 3. The reinforcing effect of glass fiber and fluorine-modified montmorillonite improves the impact and tensile strength of the material and avoids brittle fracture in acid and alkali environment; pentaerythritol stearate improves the flowability of the system, and the step-by-step mixing process ensures uniform dispersion of components, stable molding process, adaptation to existing production equipment, and no additional modification is needed. BRIEF DESCRIPTION OF DRAWINGS
[0019] FIG. 1 is a flow chart of the preparation method of the insulating powder according to the present application; FIG. 2 is a broken line comparison graph of dielectric strength and impact strength of the examples and comparative examples; FIG. 3 is a columnar comparison graph of volume resistivity retention rate after 10% hydrochloric acid immersion for 168h and dielectric strength retention rate after 10% sodium hydroxide immersion for 168h of the examples and comparative examples; FIG. 4 is a radar comparison graph of performance comparison data of the examples and comparative examples after unified dimensioning. DETAILED DESCRIPTION
[0020] According to FIGS. 1 to 4 , the specific embodiments of the present application are as follows: Example 1 Preparation of fluorine-modified montmorillonite: Take 50g of montmorillonite, add 950g of deionized water, and stir at 80℃ temperature and 500rpm stirring speed for 2 hours to prepare a 5wt% suspension. Add 5g of cetyltrimethylammonium bromide and 2g of potassium perfluorooctylsulfonate to the suspension, maintain 80℃ temperature and 500rpm stirring speed, and continue to react for 4 hours. After the reaction is completed, the product is collected by filtration, washed repeatedly with deionized water until no white precipitate is generated by adding silver nitrate solution, and no bromide ion residue is confirmed. The washed product is placed in an oven and dried at 100℃ for 8 hours, then crushed and passed through a 100 mesh sieve to obtain fluorine-modified montmorillonite with a fluorine content of 3wt%, an interlayer spacing of 2.5nm, a particle size of 1-5μm, and a water content of 0.8%.
[0021] Preparation of fluorine-modified graphene oxide-polyaniline composite material: Take 10 g of graphene oxide, add 20 L of deionized water to prepare a suspension of 0.5 mg / mL. Put the suspension in the ultrasonic instrument, ultrasonic treatment for 30 minutes at 300 W power, so that the graphene oxide is fully exfoliated. Add 0.3 g of 3-aminopropyl triethoxysilane to the treated suspension, stir at 500 rpm for 2 hours at 50°C under nitrogen atmosphere to complete the amination modification of graphene oxide. Reduce the temperature of the system to 20°C, add 30 g of aniline and 7.5 g of fluoroaniline, and stir for 30 minutes to make the monomers uniformly dispersed. Then add 10 wt% of ammonium persulfate aqueous solution, the molar ratio of ammonium persulfate to mixed monomers (aniline + fluoroaniline) is 1:1.2, and the dropwise adding time is controlled for 30 minutes. After the completion of dropwise adding, reduce the temperature of the system to 0°C, and react for 6 hours. After the reaction is completed, centrifuge at 8000 rpm for 15 minutes, and collect the precipitate. Wash the precipitate with 1 mol / L hydrochloric acid solution and deionized water alternately until the pH value of the washing liquid reaches 7.0. Place the washed product in a vacuum drying oven, dry at 60°C under a vacuum of -0.09 MPa for 12 hours, and then ball mill at a ball milling speed of 300 rpm for 1 hour to obtain a fluoro-modified graphene oxide-polyaniline composite material with a fluorine content of 5 wt%, an electrical conductivity of 8 x 10⁻⁴ S / m, and a particle size of 80-120 nm. 9 S / m, a particle size of 80-120 nm.
[0022] Preparation of cage silsesquioxane-polyimide copolymer: Take 20 g of cage silsesquioxane containing 8 silicon hydroxyl groups, add 380 g of N,N-dimethylformamide solvent, stir until completely dissolved, and prepare a 5 wt% solution. Add 86 g of 4,4'-diphenyl ether dicarboxylic acid chloride to the solution, the molar ratio of cage silsesquioxane to 4,4'-diphenyl ether dicarboxylic acid chloride is 1:8, and stir at 30°C under nitrogen atmosphere for 1 hour. Then add 64 g of 4,4'-diamino diphenyl ether, the molar ratio of 4,4'-diphenyl ether dicarboxylic acid chloride to 4,4'-diamino diphenyl ether is 1:1, and raise the temperature of the system to 60°C, and stir for 4 hours until the viscosity of the system reaches 500 cP. After the reaction is completed, slowly pour the system into 2 L of ethanol to precipitate, filter to collect the precipitate, and wash repeatedly with ethanol for 3 times. Place the washed product in a vacuum drying oven, dry at 80°C under a vacuum of -0.09 MPa for 10 hours, and then crush and pass through a 100 mesh sieve after drying to obtain a cage silsesquioxane-polyimide copolymer with a number average molecular weight of 20,000 Da, a glass transition temperature of 220°C, and a dielectric constant of 3.0 (1 MHz).
[0023] Preparation of insulating powder: S1. 13 parts of aluminum hydroxide, 7 parts of nano boron nitride (hexagonal phase, particle size 50-100 nm, purity 99.2%, surface treated with perfluorooctanoic acid, surface fluorine coverage 30%), 3 parts of nano titanium dioxide (particle size 20-30 nm, purity 99.5%), 1.5 parts of nano zinc oxide (particle size 15-25 nm, purity 99.3%) were weighed by weight parts, placed in a mixer, stirred at a stirring rate of 500 rpm for 10 minutes to make the materials preliminarily mixed uniformly. The mixed powder was transferred to an oven and dried at a temperature of 100°C for 2 hours to remove the water in the powder. After drying, cool to 40°C, add 1.5 parts of silane coupling agent KH-560 and 0.8 parts of perfluorooctyl triethoxysilane, place in a high-speed mixer, stir at a stirring rate of 1500 rpm for 30 minutes, so that the coupling agent and fluorosilane are uniformly coated on the surface of the powder.
[0024] S2. 18 parts of epoxy resin (bisphenol A type epoxy resin and fluorine-containing epoxy resin compounded at a mass ratio of 4:1, bisphenol A type epoxy value 0.48 eq / 100g, softening point 85°C; fluorine-containing epoxy resin is perfluorobutyl glycidyl ether type, fluorine content 10wt%, epoxy value 0.35 eq / 100g, softening point 70°C), 2 parts of ferrocene-based epoxy resin (epoxy value 0.42 eq / 100g, softening point 90°C), 4 parts of polytetrafluoroethylene powder (particle size 1-3 μm, purity 99.5%), 3 parts of the above prepared fluorine modified montmorillonite were added by weight parts to the above treated powder, and transferred to a twin screw mixer. The temperature of the mixer was raised to 80°C, and the melt mixing was carried out at a stirring rate of 800 rpm, and the vacuum degree in the mixer was controlled at-0.08 MPa to remove the bubbles in the system, and the mixing time was 20 minutes.
[0025] S3. The temperature of the material in the twin screw mixer was reduced to 60°C, 5 parts of melamine cyanurate (particle size 5-10 μm, purity 99.0%), 2 parts of the above prepared fluorine modified graphene oxide-polyphenylamine composite, 1 part of pentaerythritol stearate (purity 99.0%, melting point 60°C), 3 parts of the above prepared cage silsesquioxane-polyimide copolymer were added by weight parts, the stirring rate was kept at 800 rpm, and the mixing was continued for 15 minutes to ensure uniform dispersion of each component.
[0026] S4. 6 parts of glass fiber (alkali-free type, diameter 5-15 μm, length 50-150 μm, tensile strength 1800 MPa) were added by weight parts, the temperature in the mixer was kept at 50°C, the stirring rate was reduced to 300 rpm, and the stirring was carried out for 10 minutes. The material was transferred to a twin screw extruder for granulation, the feeding section temperature of the extruder was 100°C, the compression section temperature was 110°C, the homogenization section temperature was 120°C, and the die head temperature was 110°C. The obtained granules were placed in a refrigerated crusher and crushed at a temperature of-50°C, then sieved through a 200 mesh sieve to obtain the finished insulation powder.
[0027] Example 2 Preparation of fluorine-modified montmorillonite: Take 50 g of montmorillonite, add 833 g of deionized water, stir at a stirring rate of 600 rpm for 2.5 hours at a temperature of 85°C to prepare a 6wt% suspension. Add 4.5 g of hexadecyl trimethyl ammonium bromide and 2.2 g of potassium perfluorooctyl sulfonate to the suspension, maintain a temperature of 85°C and a stirring rate of 600 rpm for 5 hours to continue the reaction. After the reaction is completed, filter the product, wash repeatedly with deionized water until no bromide ion residue is detected by silver nitrate solution. Place the product in an oven, dry at a temperature of 105°C for 9 hours, crush and pass through a 100 mesh sieve after drying, to obtain fluorine-modified montmorillonite with a fluorine content of 4wt%, an interlayer spacing of 3.2 nm, a particle size of 1-5 μm, and a water content of 0.6%.
[0028] Preparation of fluorine-modified graphene oxide-polyaniline composite: Take 10 g of graphene oxide, add 13.3 L of deionized water to prepare a 0.75 mg / mL suspension. Ultrasonic treatment at a power of 350 W for 35 minutes, add 0.4 g of 3-aminopropyl triethoxysilane, stir at a stirring rate of 600 rpm for 2.5 hours under a nitrogen atmosphere at a temperature of 55°C. Reduce the temperature of the system to 22°C, add 40 g of aniline and 10 g of fluoraniline, stir for 30 minutes, then add 10wt% ammonium persulfate aqueous solution dropwise, the molar ratio of ammonium persulfate to mixed monomers is 1:1.2, the dropwise time is 35 minutes. Reduce the temperature of the system to 2°C, react for 7 hours. Centrifuge at a centrifugal rate of 9000 rpm for 18 minutes, collect the precipitate, wash to a pH value of 6.8. Dry at a temperature of 65°C and a vacuum degree of -0.09 MPa for 13 hours, ball mill at a ball milling rate of 400 rpm for 1.5 hours to obtain a composite with a fluorine content of 6.5wt%, an electrical conductivity of 7×10⁻ 9 S / m, a particle size of 90-130 nm.
[0029] Preparation of cage silsesquioxane-polyimide copolymer: Take 20 g of cage silsesquioxane containing 8 silicon hydroxyl groups, add 327 g of N,N-dimethylformamide to prepare a 6wt% solution. Add 97 g of 4,4'-diphenyl ether dicarboxylic acid chloride, the molar ratio of the two is 1:9, stir at a temperature of 35°C under a nitrogen atmosphere for 1 hour. Add 72 g of 4,4'-diamino diphenyl ether, the molar ratio of the two is 1:1, increase the temperature to 65°C, react for 5 hours until the viscosity of the system reaches 650 cP. Pour into 2.2 L of ethanol to precipitate, wash 4 times, dry at a temperature of 85°C and a vacuum degree of -0.09 MPa for 11 hours, crush and pass through a 100 mesh sieve to obtain a copolymer with a number average molecular weight of 35,000 Da, a glass transition temperature of 235°C, and a dielectric constant of 2.9 (1 MHz).
[0030] Insulating powder preparation: S1. Weigh 15 parts of aluminum hydroxide, 8.5 parts of nano boron nitride (hexagonal phase, particle size 50-100 nm, purity 99.3%, surface fluorine coverage 32%), 3.5 parts of nano titanium dioxide (particle size 20-30 nm, purity 99.6%), 2 parts of nano zinc oxide (particle size 15-25 nm, purity 99.4%), and stir at a stirring rate of 650 rpm for 12 minutes. Dry at a temperature of 110°C for 2.5 hours, cool to 45°C, add 2 parts of silane coupling agent KH-560 and 1.2 parts of perfluorooctyltriethoxysilane, and stir at a stirring rate of 1800 rpm for 35 minutes.
[0031] S2. Add 20 parts of epoxy resin (mass ratio of bisphenol A type to fluorine-containing epoxy resin 4:1, bisphenol A type epoxy value 0.50 eq / 100g, softening point 88°C; fluorine content of fluorine-containing epoxy resin 12wt%, epoxy value 0.37 eq / 100g, softening point 75°C), 2.5 parts of ferrocene-based epoxy resin (epoxy value 0.43 eq / 100g, softening point 92°C), 5 parts of polytetrafluoroethylene micro powder (particle size 1-3 μm, purity 99.6%), 4 parts of the above fluorine-modified montmorillonite, and transfer to a twin-screw mixer. Heat to 85°C, melt mix at a stirring rate of 900 rpm for 25 minutes, and vacuum to -0.085 MPa.
[0032] S3. Cool to 65°C, add 6.5 parts of melamine cyanurate (particle size 5-10 μm, purity 99.1%), 2.5 parts of the above fluorine-modified composite, 1.2 parts of pentaerythritol stearate, 3.5 parts of the above copolymer, and mix at a stirring rate of 900 rpm for 18 minutes.
[0033] S4. Add 7 parts of glass fiber (alkali-free type, diameter 5-15 μm, length 50-150 μm, tensile strength 1850 MPa), maintain the temperature at 55°C, and stir at a stirring rate of 400 rpm for 12 minutes. Twin-screw extruder granulation, feed section 105°C, compression section 115°C, homogenization section 125°C, die head 115°C. Freeze crushing temperature -45°C, pass through a 250 mesh sieve, and obtain the finished product.
[0034] Example 3 Fluorine-modified montmorillonite preparation: Take 50 g of montmorillonite, add 500 g of deionized water, stir at 90 °C temperature and 600 rpm stirring rate for 3 hours to prepare a 10 wt% suspension. Add 6 g of hexadecyl trimethyl ammonium bromide and 2.5 g of potassium perfluorooctyl sulfonate to the suspension, maintain 90 °C temperature and 600 rpm stirring rate for 6 hours to continue the reaction. After the reaction is completed, filter the product and wash repeatedly with deionized water until there is no bromide ion residue. Dry in an oven at 110 °C temperature for 10 hours, crush through a 100 mesh sieve to obtain fluorine modified montmorillonite with fluorine content of 5 wt%, interlayer spacing of 4.0 nm, particle size of 1-5 μm, and water content of 0.5%.
[0035] Preparation of fluorine modified graphene oxide-polyaniline composite material: Take 10 g of graphene oxide, add 10 L of deionized water to prepare a 1.0 mg / mL suspension. Ultrasonic treatment at 400 W power for 40 minutes, add 0.5 g of 3-aminopropyl triethoxysilane, stir at 600 rpm stirring rate for 3 hours under 60 °C temperature and nitrogen protection atmosphere. Reduce the temperature of the system to 25 °C, add 50 g of aniline and 12.5 g of fluoraniline, stir for 30 minutes, then add 10 wt% ammonium persulfate aqueous solution dropwise, the molar ratio of ammonium persulfate to mixed monomers is 1:1.2, and the dropwise time is 40 minutes. Reduce the temperature of the system to 5 °C, react for 8 hours. Centrifuge at 10000 rpm for 20 minutes, collect the precipitate, and wash until the pH value is 7.2. Dry at 70 °C temperature and -0.09 MPa vacuum degree for 15 hours, ball mill at 500 rpm ball mill rate for 2 hours to obtain a composite material with fluorine content of 8 wt%, electrical conductivity of 6×10⁻ 9 S / m, particle size of 100-150 nm.
[0036] Preparation of cage silsesquioxane-polyimide copolymer: Take 20 g of cage silsesquioxane containing 8 silicon hydroxyl groups, add 220 g of N,N-dimethylformamide to prepare an 8 wt% solution. Add 108 g of 4,4'-diphenyl ether dicarboxylic acid chloride, the molar ratio of the two is 1:10, stir at 40 °C temperature under nitrogen protection for 1 hour. Add 80 g of 4,4'-diamino diphenyl ether, the molar ratio of the two is 1:1, increase the temperature to 70 °C, and react for 6 hours until the viscosity of the system is 800 cP. Pour into 2.5 L of ethanol to precipitate, wash 5 times, dry at 90 °C temperature and -0.09 MPa vacuum degree for 12 hours, and crush through a 100 mesh sieve to obtain a copolymer with number average molecular weight of 50,000 Da, glass transition temperature of 250 °C, and dielectric constant of 2.8 (1 MHz).
[0037] Preparation of insulating powder: S1. 17 parts of aluminum hydroxide, 10 parts of nano boron nitride (hexagonal phase, particle size 50-100 nm, purity 99.5%, surface fluorine coverage 35%), 4 parts of nano titanium dioxide (particle size 20-30 nm, purity 99.7%), 2.5 parts of nano zinc oxide (particle size 15-25 nm, purity 99.5%) were weighed by weight parts, stirred at a stirring rate of 800 rpm for 15 minutes. Dry at 120°C for 3 hours, cool to 50°C, add 2.5 parts of silane coupling agent KH-560 and 1.5 parts of perfluorooctyltriethoxysilane, stir at a stirring rate of 2000 rpm for 40 minutes.
[0038] S2. Add 22 parts of epoxy resin (mass ratio of bisphenol A type to fluorine-containing epoxy resin 4:1, bisphenol A type epoxy value 0.54 eq / 100 g, softening point 95°C; fluorine content of fluorine-containing epoxy resin 15wt%, epoxy value 0.40 eq / 100 g, softening point 80°C), 3 parts of ferrocene-based epoxy resin (epoxy value 0.45 eq / 100 g, softening point 95°C), 6 parts of polytetrafluoroethylene micro powder (particle size 1-3 μm, purity 99.7%), 5 parts of the above fluorine-modified montmorillonite, and transfer to a twin-screw mixer. Heat to 90°C, melt mix at a stirring rate of 1000 rpm for 30 minutes, vacuum degree -0.09 MPa.
[0039] S3. Cool to 70°C, add 8 parts of melamine cyanurate (particle size 5-10 μm, purity 99.2%), 3 parts of the above fluorine-modified composite, 1.5 parts of pentaerythritol stearate, 4 parts of the above copolymer, mix at a stirring rate of 1000 rpm for 20 minutes.
[0040] S4. Add 8 parts of glass fiber (alkali-free type, diameter 5-15 μm, length 50-150 μm, tensile strength 1900 MPa), keep the temperature at 60°C, stir at a stirring rate of 500 rpm for 15 minutes. Twin-screw extruder granulation, feed section 110°C, compression section 120°C, homogenization section 130°C, die head 120°C. Freeze crushing temperature -40°C, pass through a 300 mesh sieve to obtain the finished product.
[0041] Comparative Example The traditional insulation powder formulation is prepared by mixing the following components in the proportions by weight: 20 parts of bisphenol A epoxy resin (epoxy value 0.50 eq / 100g, softening point 90°C), 15 parts of aluminum hydroxide, 8 parts of untreated nano-boron nitride (hexagonal phase, particle size 50-100 nm, purity 99.0%), 1.5 parts of silane coupling agent KH-560, 5 parts of calcium carbonate (particle size 5-10 μm, purity 98.5%), 7 parts of glass fiber (alkali-free type, diameter 5-15 μm, length 50-150 μm, tensile strength 1700 MPa). Fluorine-free modified component, cage-type silsesquioxane-polyimide copolymer, ferrocenyl epoxy resin, and fluorine-modified graphene-polyaniline composite material.
[0042] The preparation process is as follows: the above components are added to a mixer in the proportions, and melt-mixed at a temperature of 85°C and a stirring rate of 800 rpm for 30 minutes, without vacuum degassing treatment during the mixing process. After the mixing is completed, it is transferred to a twin-screw extruder for granulation, with the temperature of each section of the extruder being 105°C for the feeding section, 115°C for the compression section, 125°C for the homogenization section, and 115°C for the die head. The obtained granules are frozen and crushed at a temperature of -45°C, and then sieved through a 200-mesh screen to obtain the traditional insulation powder product.
[0043] The performance comparison data of the examples and the comparative examples are as follows: Table 1 Performance index Example 1 Example 2 Example 3 Comparative example Volume resistivity (Ω·cm) 3.2 x 10 15 ]]> 4.5 x 10 15 ]]> 6.1 x 10 15 ]]> 7.8 x 10 13 ]] Dielectric strength (kV / mm) 32 34 36 21 Volume resistivity retention rate after 168 h of 10% hydrochloric acid immersion (%) 89 92 95 43 Dielectric strength retention rate after 168 h of 10% sodium hydroxide immersion (%) 88 91 94 41 Thermal conductivity (W / (m·K)) 0.88 1.02 1.18 0.52 impact strength (kJ / m 2 ) 29 31 33 17 Melt flowability (g / 10 min) 24 22 20 14 Volatile organic content (g / L) 0.28 0.24 0.21 1.6 The long-term performance indicators of the examples and the comparative examples are as follows: Table 2 Item Example 1 Example 2 Example 3 Comparative example Thermal conductivity retention rate after 50 times of alternate immersion in 5% hydrochloric acid and 5% sodium hydroxide 86 89 92 48 Volume resistivity retention rate after 1000 h of placement in a 60°C, 95% RH environment 87 90 93 45 Impact strength retention rate after 100 times of cold-heat cycle (-40°C to 150°C) (%) 85 88 91 42 As can be seen from the two comparison tables, the insulation powder of the present application is significantly superior to the traditional insulation powder in terms of comprehensive performance, acid and alkali resistance, and long-term stability.
[0044] In terms of basic performance, the volume resistivity, dielectric strength, thermal conductivity, impact strength, and melt flowability of the examples are all significantly higher than those of the comparative examples, and the volatile organic content is much lower than that of the comparative examples. In terms of acid and alkali resistance, after being soaked in 10% hydrochloric acid and 10% sodium hydroxide for 168 hours, the volume resistivity and dielectric strength retention rates of the examples are all above 88%, while those of the comparative examples are only 41%-43%.
[0045] In terms of long-term stability, under harsh conditions such as alternating acid and alkali soaking, humid heat environment, and cold and hot cycling, the performance retention rates of the examples are all above 85%, while those of the comparative examples are less than 50%. Among them, Example 3 has the best performance in terms of each performance due to its higher fluorine content and better component matching, fully proving that the present application effectively realizes the synergistic improvement of acid and alkali resistance, insulation, thermal conductivity, mechanical properties, and long-term stability through the synergy of fluorine-modified components, filler optimization, and process improvement, and solves the performance short board of traditional products.
[0046] While embodiments of the application have been shown and described, it is to be understood that the embodiments described are merely exemplary of the principles and application of the present application. Numerous modifications and adaptions can be effected without departing from the spirit and scope of the present application, which is not limited to the exact construction and arrangement described. It is intended, therefore, to cover all modifications and adaptions that fall within the scope of the claims and their equivalents.
Claims
1. An insulating powder, characterized in that, By weight parts including: epoxy resin 15-25 parts, aluminum hydroxide 10-20 parts, nano boron nitride 5-12 parts, silane coupling agent KH-560 1-3 parts, polytetrafluoroethylene micro powder 3-8 parts, fluorine modified montmorillonite 2-6 parts, melamine cyanurate 4-9 parts, nano titanium dioxide 2-5 parts, fluorine modified graphene oxide-polyphenylamine composite material 1-4 parts, pentaerythritol stearate 0.5-2 parts, nano zinc oxide 1-3 parts, glass fiber 5-10 parts, cage type silsesquioxane-polyimide copolymer 2-5 parts, ferrocene epoxy resin 1-4 parts, perfluorooctyl triethoxysilane 0.5-2 parts; by introducing fluorine element to construct a hydrophobic corrosion-resistant layer, combined with cross-linked network to enhance the structural stability, realize the excellent acid and alkali resistance and insulation performance of the synergy.
2. The insulating powder according to claim 1, characterized in that, Also includes fluorine modified montmorillonite using cetyltrimethylammonium bromide and potassium perfluorooctyl sulfonate composite modification treatment; the amount of cetyltrimethylammonium bromide is 8-12% of the mass of montmorillonite, the amount of potassium perfluorooctyl sulfonate is 3-5% of the mass of montmorillonite, the fluorine content of the modified montmorillonite is 3-5wt%, the interlayer spacing is 2.5-4.0nm, the particle size is 1-5μm, and the water content is ≤1.0%.
3. The insulating powder according to claim 2, characterized in that, Also includes the addition amount of perfluorooctyl triethoxysilane is preferably 0.8-1.5 parts, the fluorine alkyl chain in the molecule reacts with the molecular chain of epoxy resin to form a dense fluorosilane modified layer on the surface and inside of the insulating powder.
4. The insulating powder according to claim 3, characterized in that, Also include the fluorine modified graphene oxide-polyaniline composite material is prepared by fluorine aniline graft modification;The mass ratio of graphene oxide and polyaniline is 1:3-1:5, the amount of fluorine aniline is 20-25% of the mass of aniline monomer, the fluorine element content of the modified composite material is 5-8wt%, and the conductivity is ≤10⁻ 8 S / m, particle size 50-200nm.
5. The insulating powder according to claim 4, characterized in that Also includes the epoxy resin is a bisphenol A type epoxy resin compounded with a fluorine-containing epoxy resin in a mass ratio of 4:1; the epoxy value of the bisphenol A type epoxy resin is 0.48-0.54eq / 100g, and the softening point is 85-95℃; The fluorine-containing epoxy resin is a perfluorobutyl glycidyl ether type, the fluorine content is 10-15wt%, the epoxy value is 0.35-0.40eq / 100g, and the softening point is 70-80℃.
6. The insulating powder according to claim 5, characterized in that Also includes the nano boron nitride is a hexagonal structure, which is treated with perfluorooctanoic acid, the amount of perfluorooctanoic acid is 5-8% of the mass of nano boron nitride, the surface fluorine coverage of the treated nano boron nitride is ≥30%, the particle size is 50-100nm, the purity is ≥99%, and the thermal conductivity is ≥300W / (m·K).
7. The insulating powder according to claim 6, characterized in that Preferably includes by weight parts: epoxy resin 18-22 parts, aluminum hydroxide 13-17 parts, nano boron nitride 7-10 parts, silane coupling agent KH-560 1.5-2.5 parts, polytetrafluoroethylene micro powder 4-6 parts, fluorine modified montmorillonite 3-5 parts, melamine cyanurate 5-8 parts, nano titanium dioxide 3-4 parts, fluorine modified graphene oxide-polyphenylamine composite material 2-3 parts, pentaerythritol stearate 1-1.5 parts, nano zinc oxide 1.5-2.5 parts, glass fiber 6-8 parts, cage type silsesquioxane-polyimide copolymer 3-4 parts, ferrocene epoxy resin 2-3 parts, perfluorooctyl triethoxysilane 0.8-1.5 parts; the preferred formula keeps ≥88% of the performance after soaking in 10% hydrochloric acid and 10% sodium hydroxide solution for 168 hours.
8. A process for the production of the insulating powder according to claim 7, characterized in that, Includes: S1, aluminum hydroxide, nano boron nitride, nano titanium dioxide, nano zinc oxide were weighed by parts by weight, placed in a mixer and stirred at 500-800 rpm for 10-15 minutes to mix evenly; transferred to an oven and dried at 100-120°C for 2-3 hours to remove moisture, cooled to 40-50°C, then added silane coupling agent KH-560 and perfluorooctyl triethoxysilane, placed in a high-speed mixer and stirred at 1500-2000 rpm for 30-40 minutes to evenly coat the powder surface with the coupling agent and fluorosilane; S2, add epoxy resin, ferrocene-based epoxy resin, polytetrafluoroethylene powder, fluorine-modified montmorillonite, transfer to a twin-screw mixer, heat to 80-90°C, melt and mix, stir at 800-1000 rpm for 20-30 minutes, control the vacuum degree to -0.08 to -0.09 MPa to remove bubbles and enhance the compatibility of the components; S3, cool to 60-70°C, add melamine cyanurate, fluorine-modified graphene oxide-polyphenylamine composite, pentaerythritol stearate, cage-type silsesquioxane-polyimide copolymer, maintain stirring at 800-1000 rpm for 15-20 minutes to ensure uniform dispersion of each component; S4, add glass fiber, cool to 50-60°C, reduce the stirring rate to 300-500 rpm and stir for 10-15 minutes; transfer to a twin-screw extruder for granulation, the extruder zone temperatures are 100-110°C for the feeding section, 110-120°C for the compression section, 120-130°C for the homogenization section, and the die temperature is 110-120°C; freeze and crush to -50 to -40°C, pass through a 200-300 mesh sieve to obtain the finished product.
9. The method of claim 8, wherein the insulation powder is prepared by a process comprising: The preparation method of the fluorine-modified montmorillonite includes: weighing montmorillonite and adding it to deionized water to prepare a 5-10 wt% suspension, stirring at 500-600 rpm for 2-3 hours at 80-90°C to fully exfoliate and disperse the montmorillonite; add cetyltrimethylammonium bromide and potassium perfluorooctyl sulfonate to the suspension, the amount of cetyltrimethylammonium bromide is 8-12% of the mass of montmorillonite, and the amount of potassium perfluorooctyl sulfonate is 3-5% of the mass of montmorillonite, maintain 80-90°C and 500-600 rpm stirring for 4-6 hours to insert the modifier into the interlayer of montmorillonite; after the reaction is completed, filter the product, wash repeatedly with deionized water until there is no bromide ion in the filtrate, dry in an oven at 100-110°C for 8-10 hours, crush and pass through a 100 mesh sieve to obtain fluorine-modified montmorillonite.
10. The method of claim 8, wherein the insulation powder is prepared by a process comprising: The preparation method of the fluorine-modified graphene oxide-polyaniline composite material comprises the following steps: taking graphene oxide and adding it into deionized water to prepare a suspension with a concentration of 0.5-1.0 mg / mL, and then performing ultrasonic treatment at 300-400 W for 30-40 minutes; adding 3-aminopropyl triethoxysilane with a mass fraction of 3-5% of the graphene oxide, and stirring at 500-600 rpm under nitrogen protection at 50-60 DEG C for 2-3 hours to complete the amination modification; cooling to 20-25 DEG C, adding aniline and fluoraniline mixed monomers, the mass ratio of aniline to fluoraniline being 4:1, and the mass ratio of graphene oxide to the total mass of the mixed monomers being 1:3-1:5, and then adding 10 wt% ammonium persulfate solution dropwise after stirring for 30 minutes, the molar ratio of ammonium persulfate to the mixed monomers being 1:1.2, and the dropwise adding time being 30-40 minutes; cooling to 0-5 DEG C and reacting for 6-8 hours; collecting the product by centrifugation at 8000-10000 rpm for 15-20 minutes, washing with 1 mol / L hydrochloric acid and deionized water alternately until the pH is 6.5-7.5, vacuum drying at 60-70 DEG C for 12-15 hours, and ball milling at 300-500 rpm for 1-2 hours to obtain the fluorine-modified graphene oxide-polyaniline composite material.
Citation Information
Cited By
Nanometer type multifunctional negative ion material and preparation method thereof
CN121488974A
High-temperature-resistant damp-heat-resistant epoxy structural adhesive and preparation method thereof
CN121610225A
Insulated power cable and preparation method thereof
CN121748058A